1988
DOI: 10.1007/bf00379957
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk and habitat selection in the persistence of a remnant caribou population

Abstract: A small caribou herd of 24-77 animals resided on Pic Island (1138 ha) in Lake Superior from 1976 to 1984. Most of the caribou populations on the adjacent mainland had gone extinct earlier in this century. We tested three hypotheses for the persistence of this remanant population: (1) there was more forage available on the island than the mainland, (2) the animals on the island were isolated from white-tailed deer and did not develop the meningeal worm infection, and (3) there was less predation by wolves on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 38 publications
1
64
0
1
Order By: Relevance
“…The presence of wolves may have been crucial in maintaining northern range aspen stands both through predation and especially through predation risks affecting elk movement and herbivory patterns. When wolves were present, ungulate antipredator strategies may have included the avoidance of high wolf use areas (Mech, 1977;Roby, 1978;Allen, 1979;Edwards, 1983;Ferguson et al, 1988). Since wolf recolonization in the early 1970s, researchers in Canada's Banff and Jasper National Parks have found higher elk densities in low wolf predation areas (Dekker, 1985;White et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of wolves may have been crucial in maintaining northern range aspen stands both through predation and especially through predation risks affecting elk movement and herbivory patterns. When wolves were present, ungulate antipredator strategies may have included the avoidance of high wolf use areas (Mech, 1977;Roby, 1978;Allen, 1979;Edwards, 1983;Ferguson et al, 1988). Since wolf recolonization in the early 1970s, researchers in Canada's Banff and Jasper National Parks have found higher elk densities in low wolf predation areas (Dekker, 1985;White et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This same lateral cover may also obstruct the flight escape of prey (Lima, 1992). Bergerud (1985) and Ferguson et al (1988) suggested woodland caribou maternal cows should take actions to reduce the success rates of wolves and bears in encountering, detecting and capturing calves by reducing movement and using shorelines with slopes, especially on islands, such as those in Pukaskwa National Park and Neys Provincial Park. Although not statistically different, the higher slopes at caribou nursery sites than absence sites that we found in both parks are consistent with this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Space is also employed in predator avoidance by woodland caribou, which disperse to reduce preda¬ tion on calves (Bergerud & Page, 1987;Ferguson et al, 1988). The success of spacing out appears to be dependent on predator density, which is likely affected by distance from habitat used by other ungulates (i.e., moose and white-tailed deer (Odocoileus virginianus)) (Thomas, 1995).…”
Section: Spatial Scalementioning
confidence: 99%